A Systematic Review on Effects of Plant-Based Diets on Outcomes Related to Glucose Metabolism - Yanto, Dwi; Michael, Michael (International Medical Journal Corp. Ltd, 2024)
Background: The term “plant-based diet” is used for a wide range of dietary patterns, and comprise all diets based mainly on food derived from plants. “Plant food” typically refers to vegetables, fruit, grains, seeds, legumes, pulses, fungi, and nuts, and a similarity among the different plant-based diets is the limited consumption of foods of animal origin. Methods: This systematic review focused on full-text English literature published between 2014 and 2024 using the PRISMA 2020 guidelines. Editorials and review pieces published in the same journal as the submission without a DOI were not accepted. Result: Five publications were found to be directly related to our ongoing systematic examination after a rigorous three-level screening approach. Subsequently, a comprehensive analysis of the complete text was conducted, and additional scrutiny was given to these articles. Conclusion: A dietary pattern excluding foods of animal origin is likely to have beneficial effects on glucose metabolism in individuals with T2DM and overweight/obesity